The Phenomenon of Sexual Violence among Adolescents in the Jurisdiction of the West Jakarta National Police Resort and Its Prevention Efforts - Dylan Aldianza Ramadhan; Charina Putri Besila (Universitas Lampung, 2019)
The writing of this scientific paper examines the lack of legal awareness of the community about sexual violence. This scientific work arose because the author saw that there were still many cases of sexual violence even though there were rules governing the acts of sexual violence. And this scientific work aims to tell the public what factors influence the act of sexual violence still arise and what efforts can be made by the community and law enforcement officials such as the police for this problem and is expected to eliminate the emergence of new sexual violence. The study sample was victims of sexual violence or sexual harassment in the Jakarta Bara police station. Data collection is carried out by interviewing 15 West Jakarta District Police Polres. And also conduct literature studies by looking for sources related to sexual violence. The results of this study suggest that the factors that often underlie the occurrence of sexual violence is a love factor where if the victim refuses to serve the perpetrators things will arise that are undesirable and there are false facts from the recognition of the average perpetrator who was interrogated by the police